Since log base 12 of 1 is 0 and log base 12 of 1/12 is -1, we have:
h(1)+h^-1(-1) = 0 + (-1) = -1
Therefore, the correct answer is:
h(1)+h−1(−1)=0
Given is the graph of the function h(x)=log12x. Which of the following correctly uses the graph to find h(1)+h−1(−1)?
(1 point)
Responses
h(1)+h−1(−1)=2
h left parenthesis 1 right parenthesis plus h superscript negative 1 baseline left parenthesis negative 1 right parenthesis equals 2
h(1)+h−1(−1)=3
h left parenthesis 1 right parenthesis plus h superscript negative 1 baseline left parenthesis negative 1 right parenthesis equals 3
h(1)+h−1(−1)=2.5
h left parenthesis 1 right parenthesis plus h superscript negative 1 baseline left parenthesis negative 1 right parenthesis equals 2.5
h(1)+h−1(−1)=0
h left parenthesis 1 right parenthesis plus h superscript negative 1 baseline left parenthesis negative 1 right parenthesis equals 0
1 answer